Application of Eliciting Activities (MEA) Model Learning with a Scientific Approach to Improve Mathematical Representation Skills - Dasrin Pohan; Sahat Saragih; Nerli Khairani (Study Program of Mathematics Education of Unimed Postgraduate Program, 2024)
This research aims to determine: (1) To examine the differences in increasing representational abilities and mathematical learning independence for students who are given learning using the activity elicitation model and students who are given scientific learning. (2) To learn about the process of responding to kids who learn utilizing the activity elicitation approach. Those who approach learning scientifically. This is an example of experimental study. This study's population consisted of all pupils in class VIII of SMP Asy-Syafiiyah Medan, and the research sample was drawn at random from two classes. The study's findings indicate that (1) beginning mathematics abilities have an impact on students' mathematical representation abilities and (2) abilities have an impact. Students' independence in early mathematical learning. The increase in mathematical representation abilities of students who get MEA learning and those who receive scientific approach learning differs. (2) Using the eliciting events learning model to complete student answers is superior to learning using a scientific approach. Thus, scientifically based learning activity elicitation models can be employed as an alternative in learning mathematics to increase mathematical representation abilities.